Effect of Prophylactic Negative Pressure Wound Therapy vs. Standard Wound Dressing on Surgical-Site Infection in Obese Women After Cesarean Delivery. Issue 2 (24th June 2021) - Tuuli, M.G.; Liu, J.; Tita, A.T.N.; Longo, S.; Trudell, A.; Carter, E.B.; Shanks, A.; Woolfolk, C.; Caughey, A.B.; Warren, D.K.; Odibo, A.O.; Colditz, G.; et al.
Abstract : ( JAMA . 2020;324:1180–1189) Maternal obesity is associated with greater likelihood of cesarean delivery and higher risk of surgical-site infection. While prophylactic negative pressure wound therapy using portable, single-use systems has been increasingly used following cesarean delivery, larger studies are needed to evaluate its ability to decrease infections. This study aimed to compare the effects of prophylactic negative pressure wound therapy and standard wound dressing on risk of surgical-site infections. The authors hypothesized negative pressure wound therapy would decrease infections.